Music and Knowledge: A Performer's Perspective - Dahl, Per (Brill, 2017)
This book illustrates the acquisition of knowledge in a musician$1 (Bs performative practice, and how this can contribute to the development of Artistic Research. Readership: Educational Researchers and their studentss
English
Keywords: Education; Education